Readers' Processing and Use of Source Information as a Function of Its Usefulness to Explain Conflicting Scientific Claims. Issue 5 (4th July 2019) - Gottschling, Steffen; Kammerer, Yvonne; Gerjets, Peter
ABSTRACT: The present research examines how the usefulness of source information to explain conflicting scientific claims affects laypersons' processing of this information as they seek possible explanations for the conflicting scientific claims in the sources and during resolution of the conflict. In an eye-tracking experiment, we presented 76 participants with two conflicting scientific claims (on a controversial nanotechnology issue) put forward by two scientists (sources) that did or did not differ in their implied trustworthiness. We expected differences in trustworthiness to be useful source information for claim evaluation and explanation of the conflict. This should lead to longer processing of the source information during reading, to a stronger explanation of the conflict through differences in the scientists' motivations, and to stronger agreement with the claim of the source which was more trustworthy. Our results show that differences in the sources' trustworthiness indeed led to increased visual attention to source information during reading. Moreover, the source information affected individuals' explanation of the conflict as well as their claim agreement: Individuals in the condition with differences in trustworthiness agreed more strongly with scientists' motivations as a potential explanation for the conflict and agreed more strongly with the claim of the more trustworthy source than the individuals in the control condition. These results are discussed in the context of the content-source integration (CSI) model.